2015
DOI: 10.1097/acm.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Effect

Abstract: These results suggest that creating proximity between basic science and clinical concepts may not guarantee cognitive integration. Although cause-and-effect explanations may not be possible for all domains, making explicit and specific connections between domains will likely facilitate the benefits of integration for learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…28 By comparing why content Integrated for Causation versus why content Integrated in Sequence, we show that teaching that explicitly promotes cognitive integration appears to help participants further mobilize their conceptual knowledge, which then enhances how well they transfer their learning. 24 There are three key implications for educators who want to design education that promotes transfer of learning: (1) they need to consider trainees' level of conceptual knowledge; (2) the content they choose to teach matters and should include conceptual knowledge that explains the Bwhy^; and (3) how they expose the relationships between the how and why content matters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 By comparing why content Integrated for Causation versus why content Integrated in Sequence, we show that teaching that explicitly promotes cognitive integration appears to help participants further mobilize their conceptual knowledge, which then enhances how well they transfer their learning. 24 There are three key implications for educators who want to design education that promotes transfer of learning: (1) they need to consider trainees' level of conceptual knowledge; (2) the content they choose to teach matters and should include conceptual knowledge that explains the Bwhy^; and (3) how they expose the relationships between the how and why content matters.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In studying how expertise develops, researchers have found that trainees learning to make clinical diagnoses have better diagnostic skill retention and transfer when teaching involves integrating basic science and clinical knowledge. [14][15][16][17][18][19][20][21][22][23][24][25][26] Hence, identifying and selecting the relevant conceptual and procedural knowledge appears to be a key decision point when educators choose which content to teach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These links between basic sciences and clinical content should be strong within the minds of individual learners (27,28) for cognitive integration to happen (2). Studies have also reported that cognitive integration of knowledge, which helps in the application of basic science knowledge to clinical contexts, would not happen spontaneously (15,16) just by exposing students to an integrated curriculum (15). Our study confirms the above finding that implementing an integrated curriculum alone would not be sufficient enough to prepare medical students for long-term retention and application of basic science knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive integration is defined as "conceptual, cognitive connections between different types of knowledge," occurring within the mind of the learner [1]. Previous studies suggest novices' cognitive integration of basic science and clinical concepts leads to improved diagnostic performance in this early stage of training [2][3][4][5][6][7][8][9][10]. Because cognitive integration is not directly observable, demonstrating evidence of successful cognitive integration remains a challenge.…”
Section: Introductionmentioning
confidence: 99%